Exploring monological and dialogical phases in naturally occurring explanations - Fisher, Josephine Beryl; Lohmer, Vivien; Kern, Friederike; Barthlen, Winfried; Gaus, Sebastian; Rohlfing, Katharina (KI - Künstliche Intelligenz)
Abstract Recent approaches to Explainable AI (XAI) promise to satisfy diverse user expectations by allowing them to steer the interaction in order to elicit content relevant to them. However, little is known about how and to what extent the explainee takes part actively in the process of explaining. To tackle this empirical gap, we exploratively examined naturally occurring everyday explanations in doctor–patient interactions ( N = 11). Following the social design of XAI, we view explanations as emerging in interactions: first, we identified the verbal behavior of both the explainer and the explainee in the sequential context, which we could assign to phases that were either monological or dialogical; second, we investigated in particular who was responsible for the initiation of the different phases. Finally, we took a closer look at the global conversational structure of explanations by applying a context-sensitive model of organizational jobs, thus adding a third layer of analysis. Results show that in our small sample of conversational explanations, both monological and dialogical phases varied in their length, timing of occurrence (at the early or later stages of the interaction) and their initiation (by the explainer or the explainee). They alternated several times in the course of the interaction. However, we also found some patterns suggesting that all interactions started with a monological phase initiated by the explainer. Both conversational partners contributed to the core organizational job that constitutes an explanation. We interpret the results as an indication for naturally occurring everyday explanations in doctor–patient interactions to be co-constructed on three levels of linguistic description: (1) by switching back and forth between monological to dialogical phases that (2) can be initiated by both partners and (3) by the mutual accomplishment and thus responsibility for an explanation’s core job that is crucial for the success of the explanation. Because of the explorative nature of our study, these results need to be investigated (a) with a larger sample and (b) in other contexts. However, our results suggest that future designs of artificial explainable systems should design the explanatory dialogue in such a way that it includes monological and dialogical phases that can be initiated not only by the explainer but also by the explainee, as both contribute to the core job of explicating procedural, clausal, or conceptual relations in explanations.
Keywords: Artificial Intelligence

Die Anpassungen von Erklärungen an das Verständnis des Erklärgegenstandes der Gesprächspartner - Schaffer, Michael; Lea, Budde; Schulte, Carsten; Buhl, Heike M. (52nd DGPs Congress - Abstracts)
Keywords: Cognition; Motivation; Technical Model; Mental Model; Explainer; Explainee; Qualitative Content Analysis

Understanding and Explaining Digital Artefacts - the Role of a Duality (Accepted Paper - Digital Publication Follows) - Budde, Lea; Schulte, Carsten; Buhl, Heike M.; Muehling, Andreas (Seventh International Conference on Learning and Teaching in Computing and Engineeringe)
Keywords: ⛔ No DOI found